Pengaruh Mastery Learning terhadap Kompetensi Perawat Melakukan Pengkajian dan Perawatan Luka Ulkus Diabetikum: Tinjauan Literatur - Febby Irianti Deski; Susmiati Susmiati; Widia Wati (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Competence regarding the assessment and care of diabetic ulcer wounds in nurses is needed so that wound care can be carried out properly. Research on mastery learning in learning for nurses has been carried out a lot. However, there is still a lack of a literature review that looks at how effective this learning is in increasing the competence of nurses regarding the assessment and care of diabetic ulcers. The research method used is a systematic review by identifying journal articles published online consisting of English in 2018-2023. Articles were retrieved using the search engine tools Sciencedirect, Pubmed, and ProQuest. There are 4 journals based on inclusion criteria. The results of the study show that there is an influence of mastery learning in increasing the knowledge, attitudes and skills of nurses in carrying out clinical practice.